Peran Kepemimpinan dalam Manajemen Sumber Daya Manusia: Literatur Review - M. Yusuf; Mulyadi; Zuriani Ritonga; Muchsin (Lembaga Teewan Journal Solutions, 2026)
This study aims to analyze the role of leadership in human resource management through a literature review approach. Article searches were conducted in Google Scholar, Scopus, ScienceDirect, SpringerLink, and DOAJ databases spanning 2015–2025. The selection process followed PRISMA guidelines, resulting in ten articles meeting the inclusion criteria. The analysis was conducted using descriptive narrative analysis, extracting study characteristics, key findings, and research conclusions. The synthesis of results indicates that leadership plays a strategic role in improving the effectiveness of human resource management, both directly and through the mediation of HRM practices and organizational culture. Transformational, ethical, inclusive, and strategic leadership have been shown to increase employee motivation, work engagement, innovative behavior, and performance. In addition, training practices, competency development, flexible HRM policies, and green HRM strengthen the relationship between leadership and organizational outcomes. Several studies indicate that the influence of leadership on performance is indirect and mediated by organizational culture and HRM practices. The integration of effective leadership and appropriate HRM management policies contributes to improved individual and team performance and sustainable organizational success. These findings emphasize the importance of synergy between leadership and HRM strategies to enhance organizational competitiveness across various sectors.